2021
DOI: 10.1021/acs.est.1c01001
|View full text |Cite
|
Sign up to set email alerts
|

Tellurite Adsorption onto Bacterial Surfaces

Abstract: Tellurium (Te) is an emerging contaminant and its chemical transformation in the environment is strongly influenced by microbial processes. In this study, we investigated the adsorption of tellurite [Te(IV), TeO 3 2−] onto the common soil bacterium Bacillus subtilis. Thiol-blocking experiments were carried out to investigate the role of cell surface sulfhydryl sites in tellurite binding, and extended X-ray absorption fine structure (EXAFS) spectroscopy was performed to determine the chemical speciation of the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 68 publications
1
11
0
Order By: Relevance
“…This mechanism explains the decrease of the adsorption with the pH (Figure 4). The reduction-induced oxyanion adsorption (Goff et al, 2021;Yu et al, 2018) is a possible mechanism, which is consistent with the presence of Re(VI) on the surface (Figure S1). In this mechanism, a surface thiol is covalently bound with the cationic element of the oxyanion substituting oxygen.…”
Section: Equilibrium and Kinetics Of Adsorptionsupporting
confidence: 77%
See 1 more Smart Citation
“…This mechanism explains the decrease of the adsorption with the pH (Figure 4). The reduction-induced oxyanion adsorption (Goff et al, 2021;Yu et al, 2018) is a possible mechanism, which is consistent with the presence of Re(VI) on the surface (Figure S1). In this mechanism, a surface thiol is covalently bound with the cationic element of the oxyanion substituting oxygen.…”
Section: Equilibrium and Kinetics Of Adsorptionsupporting
confidence: 77%
“…For all the adsorbents, about 60% is attributed to heptavalent rhenium, implying that the anion is reduced by adsorption. The reduction of selenate and tellurate occurs by the adsorption on bacterial surfaces (Goff et al, 2021; Yu et al, 2018). The reaction is induced by the bond formation with two vicinal thiol sites.…”
Section: Resultsmentioning
confidence: 99%
“…4f), thus enabling more efficient and directional bioconversion of the precursors towards bio-QD formation. 38,39 The anaerobically stimulated uptake and reduction of Se by the cells were supported by metal content analysis (Fig. 4e), which showed a similar Cd content but a 3.5-fold higher Se content of the bio-hybrid under anaerobic conditions over aerobic conditions after 4 h incubation.…”
Section: Resultsmentioning
confidence: 62%
“…The importance of polysaccharide variations also arose from PCA analysis, in which the vector describing these contributions distinguished unchallenged cells from those challenged ( Figure 7 ). Interestingly, Goff and coworkers (2021) recently reported that sulfhydryl groups of the proteinaceous material within EPS of Bacillus subtilis play a crucial role in binding TeO 3 2− , mediating its sorption on bacterial surfaces [ 76 ]. At this stage, it cannot be ruled out that sulfhydryl groups in the EPS of Micromonospora EPS could bind TeO 3 2− to limit its translocation into the cell cytoplasm.…”
Section: Discussionmentioning
confidence: 99%
“…However, a direct comparison between the profiles describing RSH depletion in Micromonospora growing cells with the available literature is challenging, as most studies focused on the earliest stages (up to 2.5-h) of either bacterial growth or exposure to this oxyanion. In the case of Micromonospora growing cells, RSH depletion may rely on (i) RSH groups within EPS binding with TeO 3 2− [ 76 ], (ii) Painter-type reactions, (iii) ROS detoxification [ 84 ], and (iv) the modification of RSH-rich proteins caused by oxidative stress [ 27 ]. Hypotheses (i–iii) were sustained by the detection of vibrational modes attributable to RSH-, thiolate (RS − )-, and disulfide (RSSR)-containing molecules ( Figure 6 b,c; Table S1 ).…”
Section: Discussionmentioning
confidence: 99%